The role of CCR1 expression in herpes simplex virus-induced Behçet's disease mouse model - SAYEED HASAN MD (The Graduate School, Ajou University, 2024)
The role of CCR1 expression in herpes simplex virus- induced Behçet's disease mouse model Behçet's disease (BD) is a chronic systemic inflammatory disease with unclear etiopathogenesis. C-C chemokine receptor type 1 (CCR1) ligand, C-C motif ligand 3 (CCL3) has been identified as down-regulation expression in peripheral blood leukocytes (PBL) and lymph nodes (LN), even though the protein expression of CCR1 in BD remains unclear. The objective of this study was to analyze the role of CCR1 and its ligand CCL3 in a herpes simplex virus-induced mouse model of BD. The frequencies of CCR1+ cells on the surface and in the cytoplasm of PBL and LN were analyzed by flow cytometry. The CCR1+ cells were significantly down-regulated in BD mice compared with the normal control and symptom-free control mice. Colchicine and pentoxifylline treatment improved the symptoms of BD and increased the frequencies of CCR1+ cells in BD mice. Treatment with chemokine CCL3, a ligand of CCR1, caused BD symptoms to deteriorate in 10 of 16 BD mice (62.5%) via down-regulation of CCR1+ cells. Anti-CCL3 antibody treatment ameliorated BD symptoms in 10 of 20 mice (50%) and significantly decreased the disease severity score compared with CCL3-treated BD mice (P = 0.01) via up-regulation of CCR1+ cell frequencies. In patients with BD, plasma levels of CCL3 in an active state were significantly higher than in healthy control individuals (P = 0.02). These results show that the up-regulation of CCR1+ cells was related to the control of systemic inflammation of BD in mouse models. Keywords: Behçet's disease; CCL3; CCR1; herpes simplex virus; inflammation; mouse model.
학위논문(박사)--의생명과학과,2024. 2
Keywords: Behçet's disease; CCL3; CCR1; herpes simplex virus; inflammation; mouse model